Single and consecutive 10-day remote ischemic preconditioning modify physical performance, post-exercise exerkine levels, and inflammation - Kochanowicz, Magdalena; Brzezinska, Paulina; Mieszkowski, Jan; Kochanowicz, Andrzej; Niespodzinski, Bartlomiej; Surmiak, Marcin; Reczkowicz, Joanna; Borkowska, Andzelika; Antosiewicz, Jedrzej (Frontiers in Physiology, 2024)
PurposeRemote ischemic preconditioning (RIPC) is a method of protection against induced ischemia reperfusion injury, and an increasing number of studies showed some of its inconclusive ergogenic effects in sports. RIPC involves short cycles of cuff inflation followed by its deflation which may affect many body systems. While most of the studies focus on single RIPC effects, there is insufficient data regarding training-like repeated RIPC interventions. Thus, in this study, we analyzed the effect of a single- and consecutive 10-day RIPC procedure on a single leg, focusing on the exerkine levels and changes in inflammation markers following the Wingate Anaerobic Test (WAnT).MethodsTwo single-blinded, sham-controlled protocols were designed to evaluate the 1) single (crossover study) and 2) consecutive 10-day (parallel study) RIPC effects on the WAnT performance and exercise-induced lactate, glucose, exerkine, and inflammation markers (BDNF; IL-6; IL-10; IL-15; LIF; oncostatin M). In each protocol, 37 physically active men (19.98 ± 1.17 years) were randomly assigned into two groups according to a particular study design.ResultsAn increase in participants’ mean (4.81%, p < 0.05) and peak power (6.25%, p < 0.05) during the WAnT was observed only after the consecutive 10-day RIPC. Similarly, a significant 15.5% (p < 0.05) decrease in the IL-6 concentration 120 min after the WAnT was observed only in the consecutive 10-day RIPC protocol, as well as a 12.2% (p < 0.01) increase in oncostatin M 60 min after the WAnT.ConclusionThe results demonstrate the efficacy of the consecutive 10-day RIPC procedure in modulating exercise performance and post-exercise inflammation markers.